Blood Lead Concentrations < 10 μg/dL and Child Intelligence at 6 Years of Age - Jusko, Todd A. (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Few studies provide data directly relevant to the question of whether blood lead concentrations < 10 μg/dL adversely affect children’s cognitive function. OBJECTIVE: We examined the association between blood lead concentrations assessed throughout early childhood and children’s IQ at 6 years of age. METHODS: Children were followed from 6 months to 6 years of age, with determination of blood lead concentrations at 6, 12, 18, and 24 months, and 3, 4, 5, and 6 years of age. At 6 years of age, intelligence was assessed in 194 children using the Wechsler Preschool and Primary Scale of Intelligence–Revised. We used general linear and semiparametic models to estimate and test the association between blood lead concentration and IQ. RESULTS: After adjustment for maternal IQ, HOME scale scores, and other potential confounding factors, lifetime average blood lead concentration (mean = 7.2 μg/dL; median = 6.2 μg/dL) was inversely associated with Full-Scale IQ (p = 0.006) and Performance IQ scores (p = 0.002). Compared with children who had lifetime average blood lead concentrations < 5 μg/dL, children with lifetime average concentrations between 5 and 9.9 μg/dL scored 4.9 points lower on Full-Scale IQ (91.3 vs. 86.4, p = 0.03). Nonlinear modeling of the peak blood lead concentration revealed an inverse association (p = 0.003) between peak blood lead levels and Full-Scale IQ down to 2.1 μg/dL, the lowest observed peak blood lead concentration in our study. CONCLUSIONS: Evidence from this cohort indicates that children’s intellectual functioning at 6 years of age is impaired by blood lead concentrations well below 10 μg/dL, the Centers for Disease Control and Prevention definition of an elevated blood lead level.